2014
DOI: 10.1590/s1516-35982014001000003
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting feed efficiency in dairy goats

Abstract: -The objective of this study was to present some factors affecting feed efficiency in dairy goats. To develop our work, individual and average data from performance experiments with lactating goats were used. The following variables were evaluated: gross feed efficiency, adjusted feed efficiency, dry matter intake, milk-yield, 3.5% fat-corrected milk yield, dry matter digestibility, dietary neutral detergent fiber content, different roughage-to-concentrate ratios and body weight. The statistical analyses invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
1
1
Order By: Relevance
“…An interesting feature of the results was that feed efficiency was the lowest when roughage-to-concentrate ratio was at its peak during the 0-60 day fattening period and relative to the 60-100 day period. This result does not fully concur with the findings of Oliveira et al (19), who reported that increasing the roughage-to-concentrate ratio led to poorer feed efficiency in lactating goats.…”
Section: Growth Performance Feed Intake and Feed Efficiencycontrasting
confidence: 99%
“…An interesting feature of the results was that feed efficiency was the lowest when roughage-to-concentrate ratio was at its peak during the 0-60 day fattening period and relative to the 60-100 day period. This result does not fully concur with the findings of Oliveira et al (19), who reported that increasing the roughage-to-concentrate ratio led to poorer feed efficiency in lactating goats.…”
Section: Growth Performance Feed Intake and Feed Efficiencycontrasting
confidence: 99%
“…In meat sheep, feed efficiency can be quite variable depending on the BW, breeds, and gain composition. Oliveira et al (2014), reviewing performances of dairy goats, reported that average feed efficiency in 17 studies was 1.06 kg of milk/kg of dry matter intake (varying from 1.44 to 0.74), with ranges of daily milk production that varied from 1.1 to 3.5 kg of milk. Under Brazilian conditions, Lima et al (2017) reviewed key technical efficiency and economic performances of feedlot lambs (ranging from 16 to 52 kg of BW and average daily gain ranging from 0.15 to 0.38 kg of average daily gain/d), observing values of feed efficiency equal to 210 g/kg of dry matter intake (ranging from a minimum of 140 to a maximum of 280) and feed conversion equal to 4.7 (ranging from 3.5 to 6.9).…”
Section: Production Efficiency In Sheep and Goatsmentioning
confidence: 99%